Molecular cloning, characterization and constitutive expression analysis of TLR4 gene in Pangasianodon hypophthalmus - GHODE, GAJANAN; RATHORE, GAURAV; TRIPATHI, GAYATRI; DAVANE, KASHMIRA; PRASAD, KURUCHETI PANI (The Indian Journal of Animal Sciences, 2022)
Toll like receptor (TLR) signalling pathway plays a central role in inflammatory responses through the recognition of PAMPs and DAMPs. Toll-like receptor 4 (TLR4) is well known for the recognition of LPS of gram-negative bacteria leading to production of inflammatory cytokines. Modulation of a TLR pathway gene in different tissues indicates the functional importance of the tissues in innate immunity. The aim of this study was to clone and characterize TLR4 and evaluate its constitutive tissue distribution in Pangasianodon hypophthalmus, a commercially important fish species. The study was carried out at ICAR-CIFE, Mumbai during 2017. Partial nucleotide and amino acid sequences of TLR4 were identified in P. hypophthalmus and termed as phTLR4. Bio-informatics analysis of partial sequence revealed four putative LRR domains characteristic of TLRs. Nucleotide and amino acid sequences showed varying degree of identity with TLR4 sequences from other fish species in BLASTn and BLASTp analysis. Phylogenetic analysis placed the phTLR4 close to Ictalurus punctatus. TLR4 was found to be constitutively expressed in all the tissues studied. The significantly highest expression was recorded in intestine and spleen. The lowest expression was in muscle, heart and skin. House-keeping gene ß-actin was used as an internal control. The outcome of this research will be helpful for studying mRNA expression levels of phTLR4 under different conditions in different tissues of Pangasianodon hypophthalmus.